Identification and classification of voltage disturbances in power quality studies using wavelet - fuzzy method / Ahmad Farid Abidin - Abidin, Ahmad Farid (2005)
Power Quality (PQ) problems have been classified as one important field for consumer, manufacturer and utility [1-3]. The impacts of low PQ have given massive losses in term of monetary, low quality product and increase in maintenance [4]. Low PQ is originated from various factors such as harmonic polluted system, improper grounding and magnification of voltage due to the capacitor switching [5]. These factors normally can be mitigated if the knowledge of PQ is improved. However, the PQ problem is impossible to be avoided. As far as PQ is concerned, the indices of quality of power can be upgraded if the cause of problem could be identified [6].